A new macrolactam derivative from the marine actinomycete HF-11225. (April 2018) - Chen, Hua; Cai, Kezhou; Yao, Risheng
Abstract A new macrolactam derivative, designated as nivelactam B (1 ), was isolated from the fermentation broth of marine-derived actinomycete HF-11225. Its structure was determined on the basis of spectroscopic analysis, including 1D and 2D NMR techniques, as well as ESI-MS and comparison with data from the literature. Compound1 showed weak cytotoxic and antifungal activities.